Спрединг - коровый компенсационный фактор расширяющейся Земли - Орищенко, И.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The process of increase in the oceanic terrestrial crust is presented as a result of the Earth's expansion caused by the decompaction of rocks of the asthenosphere. It is shown that the subduction appears only if the degree of the increase in the Earth's crust in the region of middle oceanic ridges exceeds that at the expense of the Earth's expansion.